Polymer tapered pillar on a fiber end fabricated by UV irradiation using a high-NA fiber - Kurisawa, Taiga; Kamiura, Yoshiki; Fujikawa, Chiemi; Mikami, Osamu (Photonics Letters of Poland, 2022)
The increasing need for single-mode fibers (SMFs) and advances in silicon photonics (SiPh) devices have led to the need for an efficient method of optical coupling between them. To achieve a higher coupling between them, a polymer tapered pillar was fabricated on the end face of the SMF by applying the optical diffraction effect and a self-written waveguide technology using a high numerical aperture (HiNA) fiber. The initial 10.4 µm spot size was reduced to 4.17 µm at 1.55 µm wavelength, and the greatest coupling efficiency of –1.01 dB was reached between an SMF with a tapered pillar and uncured resin cladding and a HiNA fiber. Full Text: PDF References R. Marchetti, C. Lacava, L. Carroll, K. Gradkowski, P. Minzioni, "Coupling strategies for silicon photonics integrated chips [Invited]", Photonics Res. 7, 201 (2019). CrossRef R. Bachelot, C. Ecoffet, D. Deloeil, P. Royer, D.-J. Lougnot, "Integration of micrometer-sized polymer elements at the end of optical fibers by free-radical photopolymerization", Appl. Opt. 40, 5860 (2001). CrossRef P. Pura, M. Szymanski, M. Dudek, L.R. Jaroszewicz, P. Marc, M. Kujawinska, "Polymer Microtips at Different Types of Optical Fibers as Functional Elements for Sensing Applications", J. Lightwave Techn. 33, 2398 (2015). CrossRef O. Mikami, R. Sato, S. Suzuki, C. Fujikawa, "Polymer Microlens on Pillar Grown From Single-Mode Fiber Core for Silicon Photonics", IEEE Photonics. Technol. Lett. 32, 399 (2020). CrossRef Y. Kamiura, T. Kurisawa, C. Fujikawa, O. Mikami, "High optical coupling efficiency of polymer microlens and pillar on single mode fiber for silicon photonics", Jpn. J. Appl. Phys. 61, SK1009 (2022). CrossRef F. Tan, H. Terasawa, O. Sugihara, A. Kawasaki, T. Yamashita, D. Inoue, M. Kagami, C. Andraud, "Two-Photon Absorption Light-Induced Self-Written Waveguide for Single-Mode Optical Interconnection", J. Lightwave Tech. 36, 2478 (2018). CrossRef H. Terasawa, O. Sugihara, "Near-Infrared Self-Written Optical Waveguides for Fiber-to-Chip Self-Coupling", J. Lightwave Technol. 39, 7472 (2021). CrossRef K. Vanmol, K. Saurav, V. Panapakkam, H. Thienpont, N. Vermeulen, J. Watté, J. Van Erps, "Mode-field Matching Down-Tapers on Single-Mode Optical Fibers for Edge Coupling Towards Generic Photonic Integrated Circuit Platforms", J. Lightwave Tech. 38, 4834 (2020). CrossRef Y. Saito, K. Shikama, T. Tsuchizawa, H. Nishi, A. Aratake, N. Sato, "Tapered Self-Written Waveguide between Silicon Photonics Chip and Standard Single-Mode Fiber", Opt. Fiber Communication Conference (OFC2020), paper W1A.2, (2020). CrossRef Y. Saito, K. Shikama, T. Tsuchizawa, N. Sato, "Tapered self-written waveguide for a silicon photonic chip I/O", Opt. Lett. 47(12), 2971 (2022). CrossRef N.A. Baharudin, C. Fujikawa, O. Mitomi, A. Suzuki, S. Taguchi, O. Mikami, S. Ambran, "Tapered Spot Size Converter by Mask-Transfer Self-Written Technology for Optical Interconnection", Photon. Technol. Lett. 29, 949 (2017). CrossRef H. Nawata, K. Ohmori, Proc. International Conference on Electronics Packaging (ICEP), paper 23 (2014) DirectLink S. J. Frisken, "Light-induced optical waveguide uptapers", Opt. Lett. 18, 1035 (1993). CrossRef Y. Obata, Y. Oyama, H. Ozawa, T. Ito, O. Mikami, T. Uchida, "Multi-array Self-written Waveguides using Photo-mask for Optical Surface Mount Technology", International Conference on Electronics Packaging (ICEP), paper 225 (2005). DirectLink P. Yin, J.R. Serafini, Z. Su, R. Shiue, E. Timurdogan, M.L. Fanto, S. Preble, "Low connector-to-connector loss through silicon photonic chips using ultra-low loss splicing of SMF-28 to high numerical aperture fibers", Opt. Expr. 27, 24188 (2019). CrossRef https://coherentinc.force.com/Coherent/UHNA3?cclcl=en_US, (18/09/2022). DirectLink